COMPARATIVE ANALYSIS OF ECONOMIC ORDER QUANTITY (EOQ) AND JUST IN TIME (JIT) METHODS ON SUPPLY CONTROL OF PURE COCONUT WATER IN UD. MITRA NATA PERDANA IN MALANG CITY - Marselo Marselo; Cakti Indra Gunawan; Jatmiko Setiaji (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Abstract : The main problem in raw material inventory control is the importance of determining the right amount of inventory so that excess or shortage of inventory does not occur. If there is too much inventory, the company will incur large holding and ordering costs, and if it is too little, production will be hampered and the company will lose resources. Therefore, it is necessary to plan and control inventory so as not to affect company profits. The purpose of this study was to determine the calculation and comparison of raw material inventory control using the Economic Order Quantity (EOQ) and Just In Time (JIT) methods at UD. Mitra Nata Perdana in the city of Malang. This type of research is a comparative research that compares the Economic Order Quantity (EOQ) method with the Just In Time (JIT) method for the efficiency of inventory costs at UD. Mitra Nata Perdana in the city of Malang. Data collection techniques with observation, interviews, and documentation. The results showed that there were significant differences between the use of the EOQ and JIT methods in raw material inventory control. From the results of the analysis and calculations that have been done it is known that UD. Mitra Nata Perdana is more effective in using the EOQ method. This is due to the characteristics and production requirements used by UD. Mitra Nata Perdana in the city of Malang. Keywords : Inventory Control, Raw Materials, Economic Order Quantity (EOQ), Just In Time (JIT), Effectiveness.